2015
DOI: 10.1371/journal.pone.0124426
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Leukocyte Telomere Length in HIV-Infected and Uninfected Individuals: Evidence of Accelerated Cell Senescence in HIV-Associated Chronic Obstructive Pulmonary Disease

Abstract: Combination antiretroviral therapy (cART) has extended the longevity of human immunodeficiency virus (HIV)-infected individuals. However, this has resulted in greater awareness of age-associated diseases such as chronic obstructive pulmonary disease (COPD). Accelerated cellular senescence may be responsible, but its magnitude as measured by leukocyte telomere length is unknown and its relationship to HIV-associated COPD has not yet been established. We measured absolute telomere length (aTL) in peripheral leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 32 publications
3
50
1
Order By: Relevance
“…Ultimately, a critical telomere length is reached whereby cell proliferation ceases and apoptosis ensues. We have previously demonstrated that peripheral leukocyte telomere lengths in PLWH are significantly shorter than in HIV-negative control subjects, with the severity of lung function as measured by forced expiratory volume in 1 second (FEV1) correlating with decreased telomere length [4]. In this study, we further these findings by determining whether advanced replicative senescence can also be observed within the lungs of PLWH.…”
Section: To the Editormentioning
confidence: 69%
“…Ultimately, a critical telomere length is reached whereby cell proliferation ceases and apoptosis ensues. We have previously demonstrated that peripheral leukocyte telomere lengths in PLWH are significantly shorter than in HIV-negative control subjects, with the severity of lung function as measured by forced expiratory volume in 1 second (FEV1) correlating with decreased telomere length [4]. In this study, we further these findings by determining whether advanced replicative senescence can also be observed within the lungs of PLWH.…”
Section: To the Editormentioning
confidence: 69%
“…The relationship of HIV infection to several biological aging-related pathophysiologic pathways has provided some support for this hypothesis [5760]. Conversely, several recent epidemiologic studies provide support for an accentuated rather than accelerated aging-related process in the HIV-infected population, with no difference in the mean age at onset of several aging-related disease conditions between HIV-infected and uninfected persons [61, 62].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified biomarkers (e.g., soluble CD14, leukocyte telomere length) which may correlate with radiographic changes in HIV. 10,26 We do not have biomarker data to determine how levels of lung inflammation correlate with CT findings and HIV status. Currently, longitudinal CT scan data is not available to determine how CT findings may progress over time.…”
Section: Discussionmentioning
confidence: 99%